The trustworthy leader : leveraging the power of trust to transform your organization - Lyman, Amy, 1956- (Jossey-Bass, a Wiley Imprint, 2012)
"How leaders from the best workplaces build trust in their organizations. The Trustworthy Leader reveals the benefits organizations enjoy when trustworthy behavior is practiced consistently by their leaders. Drawing from examples from the Best Companies to Work For, Lyman, cofounder of Great Place to Work® Institute, explains that being trustworthy means that leaders' behaviors are rooted in their commitment to the value of trust and not simply in an imitation of the practices of others. She identifies six elements that reflect a leader's trustworthiness: honor, inclusion, engaging followers, sharing information, developing others, and moving through uncertainty to pursue opportunities. Features leaders from great companies such as REI, Wegman's, R.W. Baird, TDIndustries, and more. Based on more than 20 years of rigorous research into the value of trust in companies large and small and its link to financial and organizational performance. Published to coincide with the release of the FORTUNE 100 Best Companies to Work For® 2012 list. This book offers a key to developing high levels of trust, a critical endeavor in an age when seemingly every day a story of a leader's lapse in ethical behavior makes headlines"--